2020
DOI: 10.1038/s41598-020-65606-9
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analysis reveals the importance of epithelial-mesenchymal transition in the development of endometriosis

Abstract: Background: Endometriosis is a frequently occurring disease in women, which seriously affects their quality of life. However, its etiology and pathogenesis are still unclear. Methods: To identify key genes/ pathways involved in the pathogenesis of endometriosis, we recruited 3 raw microarray datasets (GSE11691, GSE7305, and GSE12768) from Gene Expression Omnibus database (GEO), which contain endometriosis tissues and normal endometrial tissues. We then performed in-depth bioinformatic analysis to determine dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…In this study, Hallmark pathway enrichment analysis disclosed coagulation and epithelial-mesenchymal transition (EMT) were the most significant pathways in EMs 30 – 32 . To EMT, many studies have revealed its main role in the development of EMS and Yihua Wang et al have also confirmed this by bioinformatic analysis 33 .…”
Section: Discussionmentioning
confidence: 89%
“…In this study, Hallmark pathway enrichment analysis disclosed coagulation and epithelial-mesenchymal transition (EMT) were the most significant pathways in EMs 30 – 32 . To EMT, many studies have revealed its main role in the development of EMS and Yihua Wang et al have also confirmed this by bioinformatic analysis 33 .…”
Section: Discussionmentioning
confidence: 89%
“…EVs have been isolated and characterized from peritoneal fluid, serum, cultured stromal cells from eutopic and ectopic endometrium, and peritoneal macrophages of women with endometriosis 70,93‐96 . Altered expression of genes associated with EVs is also observed in endometriotic tissue as compared to eutopic endometrium 36,97,98 …”
Section: Extracellular Vesicles In Disorders Of Endometriummentioning
confidence: 99%
“…Unfortunately, there are still no early diagnostic tools or radical treatments for this disease owing to the diversity of its symptoms and complexity of its pathogenesis 6,7 . Therefore, the most urgent task is to deeply investigate the pathophysiological basis of this disease 8,9 …”
Section: Introductionmentioning
confidence: 99%